O igri in delu - Turk Niskač, Barbara (Ethnologica - Dissertationes, 2021)
The monograph introduces the concept of work, which is inherent in human being as is play. This concept of work can be understood simultaneously as a powerful means of socialisation and as a disciplining instrument. The author problematizes the dichotomy between play and work as a construct that emerged in the specific historical and geographical context of early industrialization. She introduces the educational value attributed to work and presents how this understanding of work has historically changed through different political and socio-economic circumstances. Drawing on ethnographic studies and theorising from the fields of psychology, sociology, cultural anthropology, and social anthropology, the author analyses why and how preschool children participate in everyday work at home and in kindergarten. The author draws connections between children's participation in work and children's sociality and intersubjectivity as core human capacities as social beings. Preschool children are included as research participants along with adults, and by presenting their perspectives, this volume demonstrates the complexity of social life from an early age.